Estimating the intensity of choice in a dynamic mutual fund allocation decision - David Goldbaum; Bruce Mizrach (Rutgers University, Department of Economics, 2005)
The paper analyzes the intensity of choice in an agent based financial optimization problem. Mean-variance optimizing agents choose among mutual funds of similar styles but varying performance. We specify a model for the allocation of new funds, switching between funds, and withdrawals and obtain statistically significant estimates of the intensity of choice parameter. This estimate is also given economic interpretation through the underperformance of funds that use an active style. We find that agents will move 5% of the funds from active to passive for an extra 28 basis points of return.
Keywords: G11; 330; heterogenous agents; intensity of choice; mutual funds; Investmentfonds; Anlageverhalten; Dynamisches Modell; Theorie; Diskrete Entscheidung